IMPLEMENTATION OF ACTIVITY-BASED COSTING IN DETERMINING INPATIENT RATES AT RSUD RADEN MATTAHER JAMBI - Patmalarsih, Abdila Rungki; Yudi, Yudi; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2026)
The Activity-Based Costing (ABC) approach is a more sophisticated and accurate solution for tracing the source of costs. This study aims to provide empirical contributions regarding the relevance of applying ABC in determining more accurate inpatient rates at RSUD Raden Mattaher Jambi. Using a descriptive qualitative approach and case studies, this research explores how the application of ABC principles can improve cost allocation transparency, operational efficiency, and assist managerial decision-making. The findings indicate an overcost of 30% for the VIP class and 28% for the VVIP class, while the I, II, and III classes experienced undercosts of 6%, 38%, and 88%, respectively. The current inpatient rates applied by the hospital are Rp 1,187,803 for the VVIP class, Rp 807,683 (VIP), Rp 638,666 (Class I), Rp 551,901 (Class II), and Rp 469,900 (Class III). Therefore, the researchers hope that RSUD Raden Mattaher Jambi can process the costs incurred by the hospital and record the latest data on facilities and infrastructure in greater detail, ensuring that all information aligns with on-site conditions to identify areas of waste, improve efficiency, and optimize resource management in response to market dynamics and the evolving needs of patients.